Germination and Simulated Gastrointestinal Digestion of Chickpea (Cicer arietinum L.) in Exhibiting In Vitro Antioxidant Activity in Gastrointestinal Epithelial Cells - Ashley Newton; Kaustav Majumder (MDPI AG, 2023)
Plant-based proteins, in particular pulse proteins, have grown in popularity worldwide. Germination, or sprouting, is an effective method to release peptides and other dietary compounds. However, the combination of germination and gastrointestinal digestion in enhancing the release of dietary compounds with potential health-beneficial biological activity has yet to be entirely elucidated. The present study illustrates the impact of germination and gastrointestinal digestion on the release of dietary compounds with antioxidant activity from chickpeas (Cicer arietinum L.). Germination up to 3 days (D0 to D3) increased the peptide content by denaturing chickpea storage proteins and increased the degree of hydrolysis (DH) in the gastric phase. The antioxidant activity was measured at three different dosages (10, 50, and 100 μg/mL) and compared between D0 and D3 on human colorectal adenocarcinoma cells (HT-29). A significant increase in antioxidant activity was observed in the D3 germinated samples in all three tested dosages. Further analysis identified 10 peptides and 7 phytochemicals differentially expressed between the D0 and D3 germinated samples. Among the differentially expressed compounds, 3 phytochemicals (2',4'-dihydroxy-3,4-dimethoxychalcone, isoliquiritigenin 4-methyl ether, and 3-methoxy-4,2',5'-trihydroxychalcone) and 1 peptide (His-Ala-Lys) were identified only in the D3 samples, indicating their potential contribution towards the observed antioxidant activity.